A c-Cbl/Cbl-b antagonist inhibits EGFR ubiquitylation and sustains EGFR phosphorylation to enhance corneal re-epithelialization - Kate Tarvestad-Laise; Robert C. Monsen; Brandon L. M. Crotchett; Jamie S. Rush; Srinivasrao Ganipisetti; Rajachandrasekhar Valmon; Lynn DeLeeuw; Joseph Burlison; John O. Trent; Brian P. Ceresa (Proceedings of the National Academy of Sciences, 2026)
Growth factor receptor signaling is a critical component of tissue growth, homeostasis, and wound healing. However, receptor desensitization limits the use of exogenous growth factors as a restorative agent therapeutically. An example of this is the epidermal growth factor receptor (EGFR) in the corneal epithelium. Despite laboratory data indicating that EGFR activity accelerates corneal re-epithelialization in mice and rabbits, the clinical administration of EGF to damaged corneal epithelium has limited impact due to the attenuated signaling that occurs following sustained growth factor administration. We hypothesized that inhibition of receptor desensitization would prolong receptor activity and enhance tissue homeostasis. Having previously identified the E3 ubiquitin ligase, c-Cbl, as a key negative regulator of EGFR signaling in the corneal epithelium, we have developed a class of small molecule inhibitors of EGFR binding to CBL family proteins using virtual screening with experimental validation. Through multiple rounds of structural optimization, we have identified compound 3-120. This compound was designed to compete with phosphotyrosine 1045 of the EGFR for binding to c-Cbl. Compound 3-120 binds to c-Cbl with an ~10-fold higher affinity than phosphoEGFR, reduces EGFR ubiquitylation by 40%, and increases the magnitude of ligand-stimulated EGFR phosphorylation by 30 to 40%. Ultimately, this compound can enhance the restoration of corneal epithelial debridement wounds. Thus, compound 3-120 is an antagonist that specifically disrupts EGFR ubiquitylation to sustain receptor signaling.